A comparative survey on data encryption Techniques: Big data perspective. (2021) - Matta, Priya; Arora, Minit; Sharma, Deepika
Abstract: The prime aspect in data handling is the invulnerability of Data, therefore, Encryption is the most conventionally used technique for data security. for instance, Data Encryption Standard (DES), Rivest–Shamir-Adleman (RSA), Advanced Encryption Standard (AES) to attain it moreover, with the exponentially growing of data over time leads to the concept of Big Data which involves not only the structured but also unstructured data such as images, audio, video, and other data formats. Encrypting such varied and immense data is a challenge in itself. In this paper, we delve into some of the major algorithms and techniques for efficient encryption and decryption of the data. Moreover, we have also done a comparative analysis of the different encryption and decryption techniques to predict the use of these techniques based on application requirements. The main objective of this work is to convey a better focus on data encryption approaches and to bring out the major issues and application areas where these encryption algorithms best suit.